2020
DOI: 10.1021/acs.jmedchem.0c01376
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Opioid-Neurotensin Multitarget Peptides: From Design to Structure–Activity Relationship Studies

Abstract: Fusion of nonopioid pharmacophores, such as neurotensin, with opioid ligands represents an attractive approach for pain treatment. Herein, the μ-/δ-opioid agonist tetrapeptide H-Dmt- d -Arg-Aba-β-Ala-NH 2 ( KGOP01 ) was fused to NT(8-13) analogues. Since the NTS1 receptor has been linked to adverse effects, selective MOR-NTS2 ligands are preferred. Modifications were introduced within the native NT sequence, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…It could, therefore, be suggested that the impact of NK2 and NK3 pharmacophores on opioid activity will strongly depend on the nature of the opioid pharmacophore. The data suggest that anchorage of any C -terminal appendage to the constrained structure of KGOP01 is more tolerated, which is in line with previous studies [ 19 , 38 , 39 ]. In light of the promising opioid data, the KGOP01-based hybrids were therefore selected for further biological evaluation, and NK2 and NK3 receptor binding assays were performed.…”
Section: Discussionsupporting
confidence: 91%
“…It could, therefore, be suggested that the impact of NK2 and NK3 pharmacophores on opioid activity will strongly depend on the nature of the opioid pharmacophore. The data suggest that anchorage of any C -terminal appendage to the constrained structure of KGOP01 is more tolerated, which is in line with previous studies [ 19 , 38 , 39 ]. In light of the promising opioid data, the KGOP01-based hybrids were therefore selected for further biological evaluation, and NK2 and NK3 receptor binding assays were performed.…”
Section: Discussionsupporting
confidence: 91%
“…While the incorporation of an unnatural amino acid could be limited to a substitution, an extensive variety of backbone modifications could be inserted [41,42]. The introduction of peptoids, βand γ-amino acids, azapeptides, N-methylation, and reduced peptide bonds are only some of the common modifications that may be incorporated along the peptide backbone [43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Several groups developed bifunctional analgesics intended to act on two or more receptors involved in pain transmission. In terms of structure, these molecules consist of an opioid agonist (frequently a ligand of the mu opioid receptor) and an agonist that blocks a certain element of pronociceptive system, e.g., neurokinin-1 (NK-1) [ 9 , 10 ] cholecystokinin (CCK) [ 11 , 12 ], neurotensin (NT) [ 13 ], nociceptin (NOP) [ 14 ], and neuropeptide FF (NPFF) [ 15 ] receptors.…”
Section: Introductionmentioning
confidence: 99%